Communication Strategy of BAZNAS Da'i in Preaching Among Muslim Minorities in Karo Regency - Ayu Wahyuni Hasibuan; Sahdin Hasibuan; Hasrat Efendi Samosir (Budapest International Research and Critics University, 2021)
This type of research is qualitative research. is research that does not use abbreviations of signs or attributes. Force and Krik understand qualitative research as specific customs in social teaching which essentially hold people's views in their own area and relate to them in their language and in their designation. Based on the results of the study in the field, the researchers found that there were several communication strategies of BAZNAS da'i in preaching to Muslim minorities in Karo Regency. During the da'i preaching in Karo Regency, many changes occurred and the results of their da'wah are quite clearly visible and we can feel together, namely, Islam is familiar, they have accepted the teachings of Islam, The five daily prayers in congregation in the mosque and prayer room, Islamic studies have been carried out and so have the devotees, the congregation increases every year, it is no longer difficult to find a mosque or prayer room, women and children are no longer ashamed to wear the hijab and show their identity as a Muslim, Tolerance between religions is very high in Karo Regency.